ORGANIZATIONAL CLIMATE AND JOB SATISFACTION: COMPARATIVE STUDY BETWEEN THE STATE INTELLIGENCE AGENCY AND THE POLRI SECURITY INTELLIGENCE AGENCY - Sang Ngurah Wiratama; Surya Dharma; Chairul M (Bajang Institute, 2021)
The phenomena of resource management practices, organizational environment and job satisfaction of human resources in both organizations are assumed to have differences considering the different characteristics of the two organizations. Therefore, this research is interested in examining how police officers perceive the organizational environment and job satisfaction felt by police officers in different organizations. The population of police officers who are in the State Intelligence Agency and the National Police Security Intelligence Agency will be the subjects of this study to obtain their perceptions of the phenomenon of organizational climate and job satisfaction. The comparative study intended in this study was conducted by comparing the perceptions of police officers in the two organizations on the organizational climate and job satisfaction.The organization is a social system where human resources are the most important factor to achieve the goals and objectives of the organization. The success of the organization in achieving its goals depends on the organizational climate in which members of human resources function and the influence on their job satisfaction in perceiving the organizational climate.